Francophone literature: the voice of French language today - Pinheiro-Mariz, Josilene; Blondeau, Nicole (Lettres Françaises, 2016)
One of the main objectives of this text is to reflect on the place of French literature today, as a source of pleasure; in this case a pleasure, according to Barthes (2014), as the delight that promotes discoveries. The characteristics of Francophone literature, such as polysemy, literariness and cultural factors (orality: oraliture in some places), make possible an approach that promotes intercultural exchange. In this perspective, this article, with emphasis on literary texts from the French-speaking world, seeks to encourage, on the one hand, the “literary” reader to move toward a type of reading that shows the amplitude of the French language in other areas; and also seeks to whet the curiosity of the “ordinary” reader. On the other hand, it is intended to enable the reader and student of French to establish an immediate contact with texts marked by a multiplicity of meanings. In fact, this overlapping of cultural diversity, called Francophonie, allows literature to seduce the reader into the pleasure of literary reading, leading him to the discovery of other cultures.